2018
DOI: 10.5194/hess-22-4981-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hydrological pathways in East African montane catchments under different land use

Abstract: Abstract. Conversion of natural forest (NF) to other land uses could lead to significant changes in catchment hydrology, but the nature of these changes has been insufficiently investigated in tropical montane catchments, especially in Africa. To address this knowledge gap, we aimed to identify stream water (RV) sources and flow paths in three tropical montane sub-catchments (27–36 km2) with different land use (natural forest, NF; smallholder agriculture, SHA; and commercial tea and tree plantations, TTP) with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 73 publications
(134 reference statements)
2
40
0
Order By: Relevance
“…Each bin in this lowermost histogram therefore represents all studies that report a groundwater (or pre‐event water) fraction that overlaps with the binned interval. The frequency describing annual variations in δ 18 O applied by Jacobs et al, , differs from the other studies.…”
Section: River Water Agesmentioning
confidence: 86%
See 2 more Smart Citations
“…Each bin in this lowermost histogram therefore represents all studies that report a groundwater (or pre‐event water) fraction that overlaps with the binned interval. The frequency describing annual variations in δ 18 O applied by Jacobs et al, , differs from the other studies.…”
Section: River Water Agesmentioning
confidence: 86%
“…The middle panel presents a histogram of young streamflow fractions reported for n =351 catchments. Data for catchments not shown in the uppermost panel but that are shown in the middle panel are from Clow et al (; n =11 catchments), Jacobs et al (; n =3 catchments), and Stockinger et al (; n =1). The bottom panel panel presents histogram of reported groundwater (or “pre‐event” water) from n =101 studies reported in Table ).…”
Section: River Water Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that controls on water ages are complex and can depend on the internal structure of the catchment and can be variously dominated by physiographical characteristics, including drainage density (Hrachowitz, Soulsby, Tetzlaff, Malcolm, & Schoups, ), topography (McGuire et al, ; Mosquera et al, ), soil cover (Hrachowitz et al, 2009), soil hydraulic properties (Heidbüchel, Troch, & Lyon, ; Muñoz‐Villers, Geissert, Holwerda, & McDonnell, ), land cover (Ma & Yamanaka, ), and their spatial variation. However, several of these characteristics can be affected by land management (e.g., Soulsby, Birkel, Geris, & Tetzlaff, ), which makes MTT a useful indicator to evaluate land use impacts on hydrological processes (Jacobs et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This framework has been applied to a variety of catchments and is considered to describe the underlying hydrological processes sufficiently well (Jehn et al, ; Maier et al, ; Windhorst et al, ). The model structure represents the conceptual understanding of the rainfall‐runoff processes reported by Jacobs, Timbe, et al (). Daily precipitation and ET pot are the only model inputs required.…”
Section: Methodsmentioning
confidence: 99%